2013
DOI: 10.1590/s0102-311x2013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Revisão sistemática dos estudos epidemiológicos sobre discriminação interpessoal e saúde mental

Abstract: Foram caracterizados estudos epidemiológicos que avaliaram a relação entre discriminação interpessoal e condições de saúde mental, atualizando revisões prévias sobre o tema. Identificaram-se 34 artigos publicados entre 2000 e 2010 no PubMed, dos quais 68% utilizaram amostras de conveniência e 82% o delineamento transversal. Observaram-se associações positivas e estatisticamente significativas entre discriminação e condições adversas de saúde mental, especialmente uso de substâncias, depressão e transtornos ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0
9

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 57 publications
3
12
0
9
Order By: Relevance
“…Differently from most studies on the theme, from North America, as observed in the review by Goto et al 9 , the present study was conducted in Brazil and it not only confirms the results found by those performed in the US, but also strengthens the generalizability of findings across countries and sociocultural contexts.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Differently from most studies on the theme, from North America, as observed in the review by Goto et al 9 , the present study was conducted in Brazil and it not only confirms the results found by those performed in the US, but also strengthens the generalizability of findings across countries and sociocultural contexts.…”
supporting
confidence: 84%
“…Although the scientific literature on discrimination and health is growing, the studies concentrate specially in the United States, even when the health condition investigated is mental health 9 . Another aspect observed in Brazilian studies on the subject is the emphasis on racial discrimination and the tendency to analyze the different kinds of discrimination separately, disregarding the intersectionality and possible combined effects of its frequency and intensity on health.…”
Section: Palavrasmentioning
confidence: 99%
“…A wide body of evidence has documented the negative health outcomes associated with experiences of racial discrimination (EOD) [1216]. However, to our knowledge, no previous study has so far estimated these health-related costs in monetary terms.…”
Section: Introductionmentioning
confidence: 99%
“…The idea that racial disparities in health are caused by biology and genetics has been discredited, and other theories have taken its place to explain the association between race and health outcomes. A stress theory has been posited, and supported by several studies that found that stress accounts for much of the difference in depressive symp- , and that race-related discrimination adversely affects health 9,33 . A more recent meta-analysis found that perceived discrimination is directly related to poorer mental health status, and experimental studies showed experiences of discrimination may produce a negative psychological stress response and a heightened physiological stress response 34 .…”
mentioning
confidence: 99%